The Web-based Internet Cafe (RIC) Raharja Ordering System - Ilamsyah, Ilamsyah; Robertz, Angelica; Fitriani, Radifa Rahma (Aptisi Transactions On Technopreneurship (ATT), 2019)
The buying and selling process is very often found in everyday life, starting from traders who sell merchandise to buyers who buy the goods. At Raharja University there is a facility called Raharja Internet Cafe (RIC) which provides services in the form of print, scan and volume documents for students. Not only that, there are also items of student supplies provided there, such as the installation of an iPad that has just been obtained, iPad accessories can also be purchased there. But the problem faced at this time is the process of ordering goods that you want to buy is still conventional, namely students must come to the RIC and order the needs that they need such as print or scan and others not only that students have to queue when they want to order their needs. This was felt to be inefficient because of the technology that has been widely applied at Raharja University. To overcome this, a product ordering system was made at Raharja Internet Cafe (RIC). The method used in this study is observation and literature study to collect data and flowcharts in designing the system. With the implementation of the ordering system on the RIC website, students are now expected not to bother queuing to order their needs because student orders can be made online, so the buying and selling process can be more practical and more efficient of course.